2021
DOI: 10.1590/fst.25820
|View full text |Cite
|
Sign up to set email alerts
|

Description of the antioxidant capacity of Calafate berries (Berberis microphylla) collected in southern Chile

Abstract: The Berberidaceae family of shrubs has about 20 species present in Chile; however, the Calafate (Berberis microphylla) native to Chilean and Argentinean Patagonia, is the most widely distributed. The objective of this study was to compare the antioxidant capacity of Calafate collected at different locations in southern Chile, specifically Aysén and Magallanes. Methods: 2000 g of Calafate berries were harvested in both regions. The fruit was lyophilized for subsequent quantification of polyphenols, anthocyanins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…Raman spectrum obtained at noncarbonized leaves shows a large fluorescent background (Figure S2A), characteristic of organic matrixes. 26 This is highly contrasting to spectra obtained at carbonized regions (Figure 3A), which shows a more ordered surface with less fluorescence, with marked D and G bands at 1330 and 1550 cm −1 , respectively. Background correct spectra recorded at several (n = 60) carbonized locations over the leaf were used to calculate the mean ratio of the D and G bands intensity, found to be 0.85 ± 0.13.…”
Section: Structural Characterizationcontrasting
confidence: 63%
See 1 more Smart Citation
“…Raman spectrum obtained at noncarbonized leaves shows a large fluorescent background (Figure S2A), characteristic of organic matrixes. 26 This is highly contrasting to spectra obtained at carbonized regions (Figure 3A), which shows a more ordered surface with less fluorescence, with marked D and G bands at 1330 and 1550 cm −1 , respectively. Background correct spectra recorded at several (n = 60) carbonized locations over the leaf were used to calculate the mean ratio of the D and G bands intensity, found to be 0.85 ± 0.13.…”
Section: Structural Characterizationcontrasting
confidence: 63%
“…Raman spectrum obtained at noncarbonized leaves shows a large fluorescent background (Figure S2A), characteristic of organic matrixes . This is highly contrasting to spectra obtained at carbonized regions (Figure A), which shows a more ordered surface with less fluorescence, with marked D and G bands at 1330 and 1550 cm –1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that all evaluated extracts significantly prevented LPS-induced NO secretion by macrophages; however, the calafate extract induced a more drastic effect than other berries [ 16 ]. Additionally, in vitro studies highlighted that it could modify the inflammatory response produced by the interaction between adipocytes and macrophages, which correlates with the high content of total polyphenols in the fruit and the concentration of anthocyanins [ 104 , 105 ]. Moreover, the relative change of iNOS and TNF-α and IL-10 mRNA expression was studied to evaluate whether these extracts would modulate the gene expression of cytokines associated with specific inflammatory pathways.…”
Section: Native Plants and Their Metabolitesmentioning
confidence: 99%
“…The small blue fruits contain carbohydrates, organic acids, and phenolic compounds, with an important antioxidant activity [6]. These properties make it a nutritional and medicinal fruit that has been used by the ancestral people, and today, it is preserved and marketed freeze-dried [7,8]. At present, this Patagonian native berry is still an underutilized fruit species and its development into a new crop is relevant for the diversification of agricultural production in Argentina [9].…”
Section: Introductionmentioning
confidence: 99%